PENERAPAN MASLAHAH MURSALAH DALAM EKONOMI ISLAM - Ahmad Qorib; Isnaini Harahap (Journal Analytica Islamica, 2016)
The use of maslahah mursalah as the source for the establishment of Islamic economic practices that previously did not exist is a necessity. This is because maslahah is at the core of all these economic developments. All forms and practices of Islamic financial innovation meant to realize maslahah. The establishment of Islamic banking, the rise of Islamic credit card to facilitate a variety of transactions, their renewal in mudaraba transactions ie collateral obligations, revenue sharing method, and others show how maslahah mursalah has role in the economic development of sharia.